The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4025/actascianimsci.v38i2.30183
|View full text |Cite
|
Sign up to set email alerts
|

<b>Carcass characteristics, meat quality, feeding behavior of Nelore heifers fed diets containing sunflower pie

Abstract: The aim was to evaluate the feeding behavior, carcass characteristics and meat quality of Nelore heifers fed sunflower pie replacing cottonseed meal. They were used 30 heifers with average initial weight of 274 kg ± 28 kg and average age of 24 months, confined for 76 days. The design was completely randomized with five treatments (0, 150, 300, 450 and 600 g kg-1 DM) and six replicates per treatment. By completing 24 hours after slaughter, it evaluated muscle conformation and degree of finish made the longissim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…Deposition of adipose tissue follows a gradual order, with intramuscular fat deposited last in a carcass (Alves et al, 2016). In a study with 15-month-old heifers, Fernandes et al (2009) observed higher mean values of intramuscular fat than those observed in this study.…”
Section: Meat Qualitycontrasting
confidence: 53%
“…Deposition of adipose tissue follows a gradual order, with intramuscular fat deposited last in a carcass (Alves et al, 2016). In a study with 15-month-old heifers, Fernandes et al (2009) observed higher mean values of intramuscular fat than those observed in this study.…”
Section: Meat Qualitycontrasting
confidence: 53%